Collaborative-Based Tashrif Lughowy in Qiroatul Kutub Learning Using the Reverso - Nidak, Khoiru; Zubaidi, Ahmad; Bahruddin, Uril (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
The large number of grammatical explanations in learning Qiroatul Kutub made students increasingly slow in understanding Arabic texts, especially in Tashrif Lughowy, which demanded many changes. In order to speed up students' understanding in short meetings, this research was important to carry out. This study aimed to develop Tashrif Lughowy learning in the project-based learning Qiroatul Kutub course using the Reverso web application and tested its feasibility. It was designed with research and development research with the ADDIE approach. Expert and product tests were conducted to assess the feasibility of the product being developed. Respondents in the product test were 36 Islamic studies students at the Indonesian Islamic University. This research was developed with an emphasis on collaborative learning. Lessons were designed with projects in the analysis of the Arabic text provided. The results of the study indicated that this product development was very feasible to use, with an expert test score of 82.6% and a product test score of 89.4%. An increase in ability was also obtained by 24.3%. Collaborative learning in Tashrif Lughowy was very helpful in accelerating student understanding and maximizing lecturers in providing feedback, accelerating student understanding in a short time. In its application, lecturers checked student project work intensively every week to get maximum feedback. Digitalization of education could accelerate the transformation of quality education, so the results of this research really needed to be applied in teaching Tashrif Lughowy in learning Qiroatul Polar with very short meetings.